The study on the functional aspects of Mosque Institution - Asif, Nayeem; Utaberta, Nangkula; Ismail, Sumarni; Shaharil, Muhammad Ihsan (Faculty of Science and Technology, Universitas Islam Negeri (UIN) Maulana Malik Ibrahim Malang, Indonesia, 2021)
It was the norm for Muslim armies during the early period that whenever a new territory was conquered, the first establishment would be a mosque. That mosque served simultaneously as the military base, administrative office, and place for congregational prayers. However, at present, the function of the mosque institution has become more diversified and flexible. This paper aims to study the historical precedence of a mosque's function and the current perception of the mosque programs. The paper adopts the qualitative method through reviewing existing literature and analyzing the data using descriptive analysis. Recommendations are made based on the findings that show that the diversification of mosque's functions. It is highly needed in the present time as the Muslim community is facing rapid socio-cultural changes. Moreover, the inclusiveness of mosque institutions is significant to ensure the participation from all strata of community. Further research on these aspects can be done to study specific mosques in selected contexts.